Researching Social Change in Bali Indigenous Marriage Private - I Nyoman Budiana; Made Oka Cahyadi Wiguna (Fakultas Hukum, Universitas Warmadewa, 2021)
This article wants to understand and analyze the phenomenon of Balinese customary life arrangements related to changes in marital procedures. To be able to produce accurate findings, social phenomena are examined in detail and in-depth through qualitative research, with a phenomenological paradigm. With this paradigm the results are obtained in the form of empirical data and in-depth understanding relating to variations in categories, properties, and attributes related to the changing phenomena of cultural traditions and adat ngerorod marriage. In detail the findings generated that in social reality, the indigenous Balinese have constructed changes in the pattern of marriage from the way of ngerorod or selarian (running together) to switch to the memadik or propose, because the pattern of memadik or ask is seen to better reflect equality and justice in society. The rationale that drives is the existence of a reaction to discriminatory customary norms; innovative faith-based constructive thinking; increasing the level of education and parental-bilateral kinship thinking. Memadik marriage by means of marriage or marriage, implies a marriage as a result of the construction of modern society.